Fishbone Strategy in Teaching English in Indonesia: a Tool Organizer for Learning EFL Reading - . Nasir (International Conference on Education and Language (ICEL), 2014)
Teaching reading is not only teaching by displaying a text but also graphic organizer. This qualitative study aims at exploring students’ perception of fishbone strategy that is implemented in learning of EFL reading which is underpinned by the principles of using of visual aids and the principles of EFL teaching reading comprehension. The third semester of  twenty elementary school teachers education students   were voluntarily willing to participate in this study by joining learning of reading using fishbone strategy. Following this, the students responded questionnaire and interview of which each question comprised factual aspect, behavior aspect, and attitudinal aspect to explore the students’ responses of fishbone strategy in learning reading. The findings from questionnaire that were confirmed with interview (1) on factual aspect revealed that the students were able to solve their difficulties in learning reading, (2) on behavior aspect revealed that it was their first learning time by using fishbone strategy in reading subject, and (3) on attitudinal aspect revealed that the students felt motivated and easy to learn reading by employing fishbone strategy due to fishbone as a helpful teaching strategy for them. The overall the results of findings on each aspect from the two instruments revealed that students’ positive perception of utilizing fishbone strategy as an appropriate tool organizer in learning EFL reading in Indonesia.